PUPUK ORGANIK CAIR DAN PUPUK KANDANG AYAM BERPENGARUH KEPADA PERTUMBUHAN DAN PRODUKSI KEDELAI (Glycine max L) - Suryawaty Hamzah (AGRIUM: Jurnal Ilmu Pertanian, 2014)
This study aims to determine the awarding of Liquid Organic Fertilizer and Manure Chicken on the growth and production of soybean and their interactions.Research using randomized block design (RBD) factorial with two factors. The first factor is the provision of Liquid Organic Fertilizer (POC) consisting of 0 cc / liter of water (P0), 2 cc / l of water (P1), 4 cc / liter of water (P2) and 6 cc / l of water (P3), whereas as the second factor is the provision of Chicken manure (K) consisting of 0 kg / plant (K0), 2.5 kg / plot (K1), 5 kg / plot (K2) and 7.5 kg / plot (K3). The variables measured were plant height, number of branches, days to flowering, harvesting age, number of pods per plant, number of seeds per plant and dry weight of 100 seeds. For plant height was measured every 2 weeks starting from the age of 2 weeks after planting to flowering plants. keywords: Glycine max l Liquid Organic Fertilizer and  Manure Chicken.